2022
DOI: 10.1093/ehjci/jeab289.016
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage structure predicts thromboembolic risk in 185 patients with crytogenic stroke/TIA without history of AF

Abstract: Funding Acknowledgements Type of funding sources: Public hospital(s). Main funding source(s): Akerhus University Hospital Dept. of Cardiology Background Cryptogenic stroke/TIA (CS) is supposed to be associated with intracardiac thrombus formation and left atrial (LA) structure, in particular thrombus formation in left atrial appendage (LAA). However, there is little evidence if thromboembolic risk is associated with LAA morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…All of these findings appear to be stigmata for increased risk of atrial fibrillation, even in patients in whom an arrhythmia has not yet been identified. Therefore, it may be reasonable for clinicians to consider anticoagulation in selected patients with TIA with these findings, for whom there is a very high suspicion for unrecognized atrial fibrillation 128 , 132 134 .…”
Section: Tailored Management Planmentioning
confidence: 99%
“…All of these findings appear to be stigmata for increased risk of atrial fibrillation, even in patients in whom an arrhythmia has not yet been identified. Therefore, it may be reasonable for clinicians to consider anticoagulation in selected patients with TIA with these findings, for whom there is a very high suspicion for unrecognized atrial fibrillation 128 , 132 134 .…”
Section: Tailored Management Planmentioning
confidence: 99%